The Cambridge handbook of digital evidence in criminal investigations / edited by Vanessa Franssen, Stanislaw Tosza. - Franssen, Vanessa; Tosza, Stanislaw (Cambridge University Press, 2025)
Authored by leading scholars in the field, this handbook delves into the intricate matter of digital evidence collection, adopting a comparative and intra-disciplinary approach. It focuses specifically on the increasingly important role of online service providers in criminal investigations, which marks a new paradigm in the field of criminal law and criminal procedure, raising particular challenges and fundamental questions. This scholarly work facilitates a nuanced understanding of the multi-faceted and cross-cutting challenges inherent in the collection of digital evidence, as it navigates the contours of current and future solutions against the backdrop of ongoing European and international policy-making. As such, it constitutes an indispensable resource for scholars and practitioners alike, offering invaluable insights into the evolving landscape of digital evidence gathering.